Polarization memory in the nonpolar magnetic ground state of multiferroic CuFeO2: Data Archive - Beilsten-Edmands, J; Foronda, F; Magorrian, S (University of Oxford, 2016)
Data was acquired during pyrocurrent/magnetocurrent measurements of single-crystal CuFeO2, to investigate ferroelectric polarization at low temperatures and high magnetic fields. A Femto transimpedance amplifier was used to convert the current to a voltage, which was integrated analytically after subtracting a flat background to give the data in the form of Polarization against Magnetic Field/Temperature. Details of the experimental processes can be found in the linked publication.